Propensity-Matched Survival Analysis of Upper Urinary Tract Urothelial Carcinomas between End-Stage Renal Disease with and without Kidney Transplantation - Luo, Hao Lun (Biomed Res Int, 2019)
Urothelial carcinoma is the most common cancer following kidney transplantation (KT) in Taiwan. Unusual presentation of upper urinary tract urothelial carcinoma (UTUC) is noted in Taiwan and China. As the post-KT-UTUC oncological course is not fully understood, the aim of this study is to identify postulated significant differences for the clinical cancer course of UTUC among end-stage renal disease (ESRD) patients with and without KT. From 2005 January to 2016 March, 194 ESRD patients underwent radical nephroureterectomy due to UTUC in our hospital. The parameters were obtained from the chart record and pathology report. SPSS version 21 software was used for all statistical analyses. Unequal matching created study groups wherein a 0.2 caliper width was performed for adjusting these confounding pathological factors. Propensity score-matching cohort was performed for each population first, and then for all the study patients. We observed that the average age of UTUC in ESRD patients after KT was younger than in those without KT. The pathological factors such as stage, bladder cancer history, papillary structure, lymphovascular invasion, and variant histology were equal in these two groups. However, younger onset (p<0.001), more multifocal tumors, and carcinomas in situ were observed in post-KT UTUC (p<0.001 and 0.006, respectively). After adjustment of pathological factors by propensity score-matched analysis, the 5-year systemic UTUC recurrence was significantly more in ESRD after KT compared with ESRD without KT (p=0.03). No obvious difference in 5-year cancer related death could be observed between these two groups (p=0.314). Post-kidney transplantation upper urinary tract urothelial carcinoma in Taiwan is relatively common, has younger onset, and is associated with aggressive pathological features. The oncologic outcome of UTUC after KT is poor in our observation, even after propensity scored-matched analysis. It indicates the immunosuppression status is still associated with more malignant UTUC behavior.